PENGEMBANGAN BAHAN AJAR "SEMESTA SAINS" UNTUK MENINGKATKAN KEMAMPUAN LITERASI SAINS SISWA KELAS 3 SD - Linda Pratiwi, - (2021)
Penelitian ini bertujuan untuk mendeskripsikan desain dan pengembangan bahan ajar yang bertajuk "Semesta Sains", mendeskripsikan implementasi bahan ajar tersebut, juga mengetahui peningkatan kemampuan literasi sains siswa kelas 3 Sekolah Dasar. Latar belakang dari penelitian ini adalah rendahnya literasi sains siswa sekolah di Indonesia menurut PISA (Programme for International Student Assessment). Selain itu, pengembangan bahan ajar untuk menunjang peningkatan kemampuan literasi sains siswa sekolah juga masih minim dijumpai. Penelitian ini menggunakan metode Design & Development (D&D) model ADDIE. Bahan ajar "Semesta Sains" ini divalidasi oleh para ahli menggunakan angket untuk menentukan kelayakan produk yang dikembangkan oleh peneliti. Bahan ajar "Semesta Sains" memperoleh skor 97,5% layak dari ahli materi dan 92,5% layak dari ahli media, dengan begitu bahan ajar "Semesta Sains" dinyatakan sangat baik (sangat valid). Pengimplementasian bahan ajar "Semesta Sains" dilakukan kepada siswa kelas 3 Sekolah Dasar dan ditemukan bahwa terdapat peningkatan kemampuan literasi sains. Oleh karena itu, dapat disimpulkan bahwa bahan ajar "Semesta Sains" layak digunakan dalam pembelajaran di kelas 3 Sekolah Dasar untuk meningkatkan kemampuan literasi sains. THE DEVELOPMENT OF "SEMESTA SAINS" BOOK TO IMPROVE SCIENCE LITERACY ABILITY FOR THIRD GRADE PRIMARY SCHOOL STUDENT Linda Pratiwi 1705850 ABSTRACT This study aims to describe the design and development of teaching materials entitled "Semesta Sains", to describe the implementation of these teaching materials, as well as to find out the increase in scientific literacy skills of 3rd-grade elementary school students. The background of this research is the low scientific literacy of school students in Indonesia according to PISA (Program for International Student Assessment). In addition, the development of teaching materials to support the improvement of scientific literacy skills of school students is also still minimal. This research uses the Design & Development (D&D) method of the ADDIE model. This "Semesta Sains" teaching material was validated by experts using a questionnaire to determine the feasibility of the product developed by the researcher. The "Semesta Sains" teaching materials scored 97.5% eligible from material experts and 92.5% eligible from media experts, thus the "Semesta Sains" teaching materials were declared very good (very valid). The implementation of the "Semesta Sains" teaching materials was carried out to 3rd-grade elementary school students and it was found that there was an increase in scientific literacy skills. Therefore, it can be concluded that the "Semesta Sains" teaching materials are suitable for use in learning in grade 3 elementary schools to improve scientific literacy skills.